Peningkatan Hasil Belajar Pengukuran dengan Realistic Mathematics Education Siswa Kelas II-D SDN Manukan Kulon: IMPROVING MEASUREMENT LEARNING OUTCOMES USING REALISTIC MATHEMATICS EDUCATION FOR CLASS II-D STUDENTS OF SDN MANUKAN KULON - Istifadah, Hidayatul (J-SES : Journal of Science, Education and Studies, 2024)
This study aims to improve the mathematics learning outcomes of measurement material in class II at SD N Manukan Kulon. The approach used is Realistic Mathematics Education. The type of research used is classroom action research with the Kemmis and McTanggart models. The research stages consist of planning, action, observation and reflection. The subjects of this study were 28 students of class II at SD N Manukan Kulon, Surabaya. Collecting data in this study using observation and tests. This test instrument tested content validity and expert judgment. The data analysis technique used is descriptive qualitative and quantitative. The success indicator is that 75% of all students are above the KKM limit. The results of the study show that the use of the RME approach can improve learning outcomes in mathematics measurement material. This is indicated by an increase in the average evaluation cycle I from 77.2 to 95.67 in cycle II. The percentage increase in students who completed was 80% from 20.45% to 85.56%.